Do Democracy and Press Freedom Reduce Corruption? : Evidence from a Cross Country Study - Shyamal K. Chowdhury (University of Bonn, Center for Development Research (ZEF), 2004)
This paper calls attention to the instrumental role of democracy and press freedom in combating corruption. As opposed to an autocracy with no or limited press freedom, a free press in a democracy can inform voters about the corruption of political representatives, and voters in turn can punish incumbents by electing opposition parties. The empirical investigation carried out in this paper shows that democracy and press freedom can have significant impact on corruption. Though corruption may persist in the short- to medium-run, an increase in voters? participation and press freedom can reduce corruption. – – Dieser Beitrag untersucht die Rolle von Demokratie und Pressefreiheit bei der Bekämpfung von Korruption. Im Gegensatz zu Autokratien, in denen Pressefreiheit vollständig oder teilweise eingeschränkt ist, kann in Demokratien eine freie Presse über die Korruption politischer Repräsentanten informieren. Darauf können Wähler reagieren, indem sie Oppositionsparteien wählen. Die empirischen Untersuchungen dieses Beitrages zeigen, dass Demokratie und Pressefreiheit einen signifikanten Einfluss auf Korruption haben. Auch wenn Korruption kurz- bis mittelfristig andauert, können eine Erhöhung der Wählerbeteiligung und Pressefreiheit Korruption reduzieren.
Keywords: 330; Korruption; Rent Seeking; Demokratie; Meinungsfreiheit; Schätzung; Welt